Kinetic analysis of PODE1–3 combustion mechanisms: towards a general framework for reaction pathways - He Liu; Yajing Yang; Yanju Wei; Abdullah Baig; Yuning Tang; Muhammad Shahid Farooq; Ning Li (Energy Storage and Saving, 2025)
Polyoxymethylene dimethyl ethers (PODEs) have emerged as promising clean alternative fuels for compression-ignition engines. The combustion characteristics of PODE vary with the degree of polymerization, necessitating a deeper understanding of their kinetic behavior. This study constructed and validated a kinetic mechanism for PODE2–3 based on a previously developed detailed kinetic mechanism for PODE1. The good performance of the proposed model in reproducing the data indicates the validity of the constructed kinetic mechanism for PODE2–3. A general framework for PODE reaction pathways was proposed, with special attention paid to the reaction kinetics of each original reaction. Three source routes of PODE reactivity were elucidated: (1) Route 1: a typical chain branching reaction after hydrogen abstraction from the primary carbon, followed by two oxygenation reactions; (2) Route 2: chain branching reactions in the decomposition of partial hydroperoxyl fuel radicals to carbonyl hydroperoxides; and (3) Route 3: chain branching reactions followed by hydrogen abstraction from secondary carbon, leading to low-polymerization fuel radicals. Routes 1 and 2 are chain-branching reaction pathways common to all PODE molecules; Route 3 is a reaction pathway exclusive to highly polymerized PODE, where low-polymerization fuel radicals in the decomposition products enhance the reactivity by continuing to react with oxygen. In contrast, PODE1 exhibited significantly lower reactivity than the other components because of the absence of Route 3 reaction pathway. The kinetic mechanism of PODE fuel reactivity as a function of the degree of polymerization was elucidated. Our findings are beneficial for the development of more precise computational models to predict the combustion behavior of PODE as an alternative fuel.